Data collection infrastructure for patient outcomes in the UK - opportunities and challenges for cell and gene therapies launching - Jesper Jørgensen; Laura Mungapen; Panos Kefalas (Taylor & Francis Group, 2019)
Background: Cell and gene therapies are associated with uncertainty around their value claims at launch due to limitations of supporting clinical data; furthermore, their high costs present affordability issues for payers. Outcomes-based reimbursement can reduce payer decision uncertainty and improve patient access, however, requires data collection infrastructure and practice to be operational. Objective: To identify indications most likely to see launch of cell or gene therapies in the UK over the next five years, and to perform a qualitative assessment of how conducive the existing data collection infrastructure and clinical practice is in facilitating adoption of outcomes-based reimbursement in the corresponding indications. Methodology: Through secondary research, we identified target indications for cell or gene therapies at a mature clinical development stage (Phase III) with EU and/or US trial sites, and assessed availability of relevant data collection infrastructures in the UK. Secondary research findings were validated through primary research (expert interviews). Key parameters considered for the suitability of existing data collection infrastructure in supporting outcomes-based reimbursement include time horizon of data collection, whether data entry is mandatory and whether infrastructure is product or therapy area-specific. Findings: We identified 58 cell or gene therapies, spanning 47 indications, 20 of which are in oncology. Oncology seems well placed for outcomes data collection (through the mandatory Systemic Anti-Cancer Treatment database), however data entry compliance can be an issue (due to resource limitations), and upgrading will be needed for the purpose of outcomes-based reimbursement. Among non-oncology indications ~two-thirds have data collection infrastructures in place, but only three come close to the requirements for outcomes-based reimbursement. Conclusions: Existing data collection infrastructure in indications with potential cell or gene therapies launches in the next five years in the UK is overall not sufficient to facilitate outcomes-based reimbursement.